2019
DOI: 10.20892/j.issn.2095-3941.2018.0304
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 overexpression in hypoxia microenvironment contributes to pancreatic carcinoma progression

Abstract: Objective Stromal interaction molecule 1 (STIM1) overexpression has been reported to play an important role in progression of several cancers. However, the mechanism of STIM1 overexpression and its relationship with hypoxia in pancreatic ductal adenocarcinoma (PDAC) remains unclear. Methods STIM1 and HIF-1α expression was tested using immunohistochemistry in tissue microarray (TMA) including pancreatic cancer and matched normal pancreatic tissues, and their relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…The authors usually used immunohistochemical staining on large cohorts and Kaplan-Meier survival analysis, to observe a correlation between high channel expression and short patient survival. This is the case for KCa3.1 (Jiang et al, 2017), STIM1 (Wang et al, 2019), TRPM8 (Liu et al, 2018), TRPV6 (Song et al, 2018), TMEM16J (Jun et al, 2017), CLIC1 (Lu et al, 2015;Jia et al, 2016), and AQP1/AQP3 (Zou et al, 2019). The same correlation was obtained on gene expression using qPCR for TRPM8 (Du et al, 2018) or TCGA for TRPM2 (Lin et al, 2018) and TMEM16A (Crottes et al, 2019).…”
Section: Prognostic Markers Of Cancer Progression and Aggressivenesssupporting
confidence: 70%
See 4 more Smart Citations
“…The authors usually used immunohistochemical staining on large cohorts and Kaplan-Meier survival analysis, to observe a correlation between high channel expression and short patient survival. This is the case for KCa3.1 (Jiang et al, 2017), STIM1 (Wang et al, 2019), TRPM8 (Liu et al, 2018), TRPV6 (Song et al, 2018), TMEM16J (Jun et al, 2017), CLIC1 (Lu et al, 2015;Jia et al, 2016), and AQP1/AQP3 (Zou et al, 2019). The same correlation was obtained on gene expression using qPCR for TRPM8 (Du et al, 2018) or TCGA for TRPM2 (Lin et al, 2018) and TMEM16A (Crottes et al, 2019).…”
Section: Prognostic Markers Of Cancer Progression and Aggressivenesssupporting
confidence: 70%
“…Even though, Ecadherin levels have shown to be upregulated, in contrary to what is usually seen in cells undergoing EMT where E-cadherin decrease in favor of N-cadherin (Gheldof and Berx, 2013). Furthermore, tissue microarray analysis showed that the STIM1 expression positively correlated with HIF-1a (Wang et al, 2019). It was further shown that similar protein expression levels of STIM1 and HIF-1a were expressed in different PDAC cell lines.…”
Section: Orai and Stimmentioning
confidence: 91%
See 3 more Smart Citations